ERP-Systeme : Architektur, Management und Funktionen des Enterprise Resource Planning - Gronau, Norbert (De Gruyter Studium, 2021)
ERP systems continue to be essential for companies of all sizes and kinds in significantly boosting productivity. Based on extensive experience gained from research and consulting projects, this book provides a vendor-neutral discussion of a range of ERP system functions. The fourth edition has been revised, updated, and corrected for use as a textbook.